2003
DOI: 10.1046/j.1365-2133.2003.05265.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of T lymphocytes and cytokines in the pathogenesis of pemphigoid gestationis

Abstract: These data suggest that an inflammatory infiltrate is involved in the production of PG bullous lesions. In particular, we assume that the Th2 cells might be implicated in the very early stages of autoimmune response and may exercise a broad influence in blister formation in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
(63 reference statements)
0
16
0
3
Order By: Relevance
“…4 5 16 Our finding of increased inflammatory cell infiltrate in the bullous skin lesions is consistent with results from previous studies. [17][18][19] This infiltrate consisted of an admixture of both acute (neutrophils, eosinophils and lymphocytes) and chronic (lymphocytes, histiocytes and plasma cells) inflammatory cells, with the acute cells being the predominant cell populations. In some lesions (pustular psoriasis, familial cutaneous peeling, chronic contact dermatitis and lichen planus atrophicus), this admixture of cells showed sharp peaking of one of the inflammatory cell components (neutrophils for pustular psoriasis and lymphocytes for the others).…”
Section: Discussionmentioning
confidence: 99%
“…4 5 16 Our finding of increased inflammatory cell infiltrate in the bullous skin lesions is consistent with results from previous studies. [17][18][19] This infiltrate consisted of an admixture of both acute (neutrophils, eosinophils and lymphocytes) and chronic (lymphocytes, histiocytes and plasma cells) inflammatory cells, with the acute cells being the predominant cell populations. In some lesions (pustular psoriasis, familial cutaneous peeling, chronic contact dermatitis and lichen planus atrophicus), this admixture of cells showed sharp peaking of one of the inflammatory cell components (neutrophils for pustular psoriasis and lymphocytes for the others).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the autoimmune blistering disorders, bullous pemphigoid, herpes gestationis and pemphigus vulgaris there is a clear Th2 response which is observed early in the disease, but it is unclear whether it comes before the full thickness epithelial disruption or as a consequence of it (Arbesman et al , 1974; Borrego et al , 1999; Bushkell and Jordon, 1983; De Pita et al , 1997; Fabbri et al , 2003; Feliciani et al , 1999; Nagel et al , 2010) (Table 1). Similarly, in the genodermatosis, epidermolysis bullosa pruriginosa (OMIM 60412) (Mellerio et al , 1999; Yamasaki et al , 1997), a skin fragility disorder caused by mutations in the COL7A1 gene, and characterized by anchoring fibril abnormalities and sublamina densa blistering, the patients have been reported to have high serum IgE and eosinophilia (McGrath et al , 1994) (Table 1).…”
Section: Skin Barrier Defects Promote Allergen Sensitization - Evmentioning
confidence: 99%
“…It is considered that HLA mismatch between mother and fetus triggers an immune response which initiates an allogenic response to placental BMZ, which then cross reacts with skin. Recent immunohistochemical studies have identified a T-cell population with a prevalent T helper (Th2) phenotype in the lesional skin of PG subjects,[4] which may be implicated in the recognition of self-antigens and production of pathogenic autoantibodies.…”
Section: Discussionmentioning
confidence: 99%